Head and neck cancers associated with exposure to the September 11, 2001 World Trade Center terrorist attacks. Issue 12 (10th February 2018) - Leeman, Jonathan E.; McBride, Sean M.; Spielsinger, Daniel; Sherman, Eric J.; Wong, Richard; Riaz, Nadeem; Lee, Nancy Y.; Tsai, Chiaojung Jillian
Abstract : Exposure at the World Trade Center (WTC) terrorist collapse site on September 11, 2001 has been associated with increased cancer risk, though observational studies have identified very few cases of head and neck cancer (HNC) in exposed individuals. Eighty seven patients were identified who presented to our institution with HNC diagnosed from 2002 to 2017 who reported WTC exposure. The annual number and proportion of WTC‐exposed HNC patients has been steadily increasing since 2002, with most cancers developing >10 years following the event. Furthermore, WTC‐exposed patients with human papillomavirus (HPV)‐positive OPC experienced significantly inferior outcomes compared with non‐WTC exposed patients with HPV+ OPC (disease free survival 80.1% vs. 65.6% at 4 years, p = 0.04). This single institution study cannot establish evidence of exposure‐mediated causation but higher recurrence rates in the WTC‐exposed HPV+ OPC population suggest a treatment refractory tumor biology and possible exposure synergism with HPV‐mediated oncogenesis. Abstract : What's new? Exposure to the toxic dust clouds at the World Trade Center (WTC) site following the 2001 terrorist attacks has been associated with increased cancer risk. A connection between WTC exposure and head and neck cancer (HNC) has not been described, however. Here, the authors identified 87 HNC patients with WTC exposure and found a steady increase in the annual numbers of identified patients, with most being diagnosed after 2011. Oncologic outcomes of HNC patients with exposure to the WTC disaster and human papillomavirus (HPV)+ status seemed worse compared with unexposed controls with HPV+ status, suggesting exposure synergism with HPV‐mediated oncogenesis.